Health Care Security Training And Its Correlation With Incident Reduction In Healthcare Environments (The Review of Diabetic Studies, 2024)
Background: Healthcare security training is an umbrella term that refers to different modes of education and hands-on practice for staff to train staff in prevention, response, and recovery from security events. By the virtue of this study the researcher had tried to evaluate the components related to healthcare security training and its relationship with the reduction in adverse incidents in selected hospitals of Saudi Arabia.    Study Objectives: The main purpose of this study is to measure healthcare security training, and incident frequency, which are related to security hazards in the healthcare environment of Saudi Arabia.Materials and Methods: Study is based on cross sectional research design and carries a sample of 220 respondents (clinical staff, administrative staff, security staff, etc.). Stratified random sampling is used in the study. Data was analyzed using One Way ANOVA on the platform of SPSS ver. 27.0. Conclusion:  Healthcare facilities with structured and frequent simulation training reported fewer workplace violence incidents, unauthorized entrance, and emergency responses than the remaining facilities. This study does note the importance of proactive security training to establish a culture of safety, preparedness, and accountability to serve its patients.